Discovery of design : searching out the Creator's secrets - DeYoung, Donald B.; Hobbs, Derrik (Green Forest, Ark. : Master Books, 2009)
"Inventors and design engineers frequently look to nature for inspiration. .... This book describes many of the useful results from this ongoing search. .... The name biomimicry is often given to this endeavor of discovering and utilizing designs from nature"--Introduction, p. 9.
Microorganisms -- The insect world -- Flight -- Underwater life -- Land animals -- People -- Vegetation -- Nonliving objects.
Includes bibliographical references (p. 224-225) and index.
Keywords: Intelligent design (Teleology) -- Miscellanea; Creationism; Bionics; Technological innovations